Menganalisis Nilai-Nilai Moral Guru dalam Profesi Keguruan - Nida Khofiyyana Hadi; Rizka Hidayati; Lailatul Fitriyah; Laelatur Rohmawati (INDO PUBLISHING, 2026)
This study aims to analyze teachers moral values in the teaching profession, particularly in their roles as educators, mentors, role models, and motivators for elementary school students. This research employs a qualitative approach using a literature review method by examining various scholarly sources from journals, books, and previous studies. The findings indicate that moral values are essential in shaping both teachers and students character. Teachers play a central role in instilling moral values such as honesty, responsibility, empathy, discipline, and fairness through exemplary behavior and consistent practices in the learning process. Professional ethics including integrity, justice, professionalism, and accountability help create a dignified educational environment. Thus, teachers moral values not only influence students character development but also enhance the integrity and dignity of the teaching profession in the modern era.